Preparation method and application of conductive coating slurry for dry-method electrode battery

By preparing conductive coating slurry in dry electrode batteries, modifying monomers are prepared by reactions such as thiophene-3-boric acid and parabenzoic acid, and processing them with cellulose and silver nitrate to form conductive fillers, the dry method is solved The problems of high hot pressing temperature and short battery life in the electrode preparation process achieve higher conductivity and longer battery life.

CN119297285APending Publication Date: 2025-01-10YUQIANG NEW MATERIALS (HUBEI) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411406148.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

In the dry electrode preparation process, the hot pressing temperature is high and the service life of the prepared batteries is short.

Method used

An intermediate is prepared by a dry electrode battery conductive coating slurry, and then a reaction with acrylic alcohol, p-methylbenzoic acid, etc. is made by reacting the intermediate. and react with hexafluoroisopropanol, acrylic acid, etc. to prepare functional monomers, and obtain binder through twin screw extrusion mechanism; at the same time, functional cellulose is produced by reacting cellulose with sodium hydroxide, etc. An organic frame structure is formed, and a conductive filler is prepared in combination with silver nitrate treatment to form a conductive coating slurry with high conductivity and structural integrity.

Benefits of technology

It improves the conductivity and structural integrity of the battery, extends the service life of the battery, and improves the battery capacity retention rate.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method and application of conductive coating slurry for a dry-method electrode battery, the conductive coating slurry comprises the following raw materials by weight: 80-100 parts of Li4Ti5O12, 10-15 parts of a conductive filler and 10-15 parts of a binder, a modified monomer and a functional monomer contain thiophene structures, so that the binder has a certain conductive effect, and the conductive coating slurry has good conductivity. Meanwhile, the conjugate energy monomer contains a fluoroalkyl structure, the anti-corrosion effect of the binder can be improved, compared with a traditional binder PVDF, the melting point is lower, the binder is more suitable for a dry-method electrode hot-pressing process, the conductive filler is made to contain a large number of through holes through an organic framework of cellulose and copper, the through holes provide a channel from electrolyte to the surface of an electrode, charge transfer is promoted, and the anti-corrosion effect of the binder is improved. The interconnection network reduces the contact resistance and improves the overall conductivity, the surface metal silver further improves the conductivity, and the interior contains a silicon supporting structure, so that the structural integrity of the conductive filler in the use process is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of dry electrode preparation, and in particular to a preparation method and application of a conductive coating slurry for a dry electrode battery. Background Art

[0002] Common energy storage devices that can power electronic products mainly include lithium-ion batteries, fuel cells, metal-air batteries, supercapacitors, battery-capacitor hybrid systems, etc. Among them, rechargeable lithium-ion batteries have become the most important type of energy storage device since their first commercialization due to their advantages such as relatively light weight, large specific energy, high energy density, small self-discharge effect, stable cyclicity and no memory effect. Traditional lithium-ion batteries use a wet slurry coating process to manufacture electrodes, which has problems such as long electrode drying time, high organic solvent recovery cost, serious environmental pollution, and limited high load of the electrode. In contrast, the dry electrode preparation process with the advantages of simple process, low cost and environmental friendliness has begun to attract the attention of researchers in recent years. The dry preparation process usually involves dry mixing the powder composed of active materials, binders and conductive agents, and then spraying it directly onto the current collector, or rolling / hot pressing it into a self-supporting electrode. Since there is no need for a solvent drying process, this simplified process can not only reduce costs, but also help control the microstructure of the electrode, but it still cannot solve the problem of the short service life of lithium batteries. Summary of the invention

[0003] The purpose of the present invention is to provide a preparation method and application of a conductive coating slurry for a dry electrode battery, which solves the problem that the hot pressing temperature of the current dry electrode preparation process is high and the service life of the prepared battery is short.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A method for preparing a conductive coating slurry for a dry electrode battery comprises the following steps:

[0006] Step A1: Thiophene-3-boric acid, p-bromobenzoic acid, sodium methoxide and toluene are mixed uniformly, and reacted at a speed of 150-200 r / min and a temperature of 65-70° C. for 2-3 hours to obtain intermediate 1; intermediate 1, allyl alcohol, p-toluenesulfonic acid and toluene are mixed uniformly, and reacted at a speed of 60-80 r / min and a temperature of 110-120° C. for 7-8 hours to obtain a modified monomer;

[0007] Step A2: Hexafluoroisopropanol, acrylic acid, p-toluenesulfonic acid and toluene are uniformly mixed, and reacted for 5-6 hours at a rotation speed of 60-80 r / min and a temperature of 110-120° C. to obtain a functional monomer, and EVA, functional monomer, modified monomer and dicumyl peroxide are added to a twin-screw extruder, and extruded and cooled at temperatures of 150° C., 155° C., 160° C., 170° C., 170° C., 170° C. and 170° C. in zones 1 to 6 to obtain a binder;

[0008] Step A3: Weigh the following raw materials in parts by weight: 80-100 parts of Li4Ti5O12, 10-15 parts of conductive filler and 10-15 parts of binder, mix the raw materials evenly, and prepare a conductive coating slurry.

[0009] Furthermore, the molar ratio of thiophene-3-boric acid and p-bromobenzoic acid in step A1 is 1:1, the amount of sodium methoxide is 2% of the total mass of thiophene-2-boric acid and p-bromobenzoic acid, the molar ratio of intermediate 1 and allyl alcohol is 1:1, and the amount of p-toluenesulfonic acid is 1% of the total mass of intermediate 1 and acrylic acid.

[0010] Furthermore, the molar ratio of hexafluoroisopropanol and acrylic acid in step A2 is 1:1, the amount of p-toluenesulfonic acid is 1.5% of the total mass of hexafluoroisopropanol and acrylic acid, the mass ratio of EVA, functional monomer, modified monomer and dicumyl peroxide is 100:15:8:2-5, and the model of EVA is VA55.

[0011] Furthermore, the conductive filler is prepared by the following steps:

[0012] Step B1: cellulose, sodium hydroxide and anhydrous ethanol are mixed evenly, reacted for 1-1.5 hours at a speed of 120-150 r / min and a temperature of 25-30° C., chloroacetic acid is added, the temperature is raised to 75-80° C., and the reaction is carried out for 2-3 hours to obtain carboxymethyl cellulose, carboxymethyl cellulose, 2-aminoimidazole, dicyclohexylcarbodiimide and DMF are mixed, reacted for 4-6 hours at a speed of 200-300 r / min and a temperature of 40-50° C. to obtain functionalized cellulose, functionalized cellulose, thioglycolic acid, sodium p-toluenesulfonate and toluene are mixed evenly, reacted for 6-8 hours at a speed of 60-80 r / min and a temperature of 110-120° C. to obtain modified cellulose;

[0013] Step B2: Tetramethylammonium hydroxide and methanol are mixed evenly, nitrogen is introduced for protection, and vinyltrimethoxysilane and deionized water are added under the conditions of a rotation speed of 150-200 r / min and a temperature of 20-25°C, and the reaction is carried out for 20-25 hours, the temperature is raised to 60-70°C, and the reaction is carried out for 45-50 hours, and the pH value is adjusted to be neutral to obtain a modifier, and functionalized cellulose, 2-methylimidazole and deionized water are mixed evenly, and copper nitrate trihydrate is added under the conditions of a rotation speed of 200-300 r / min and a temperature of 25-30°C, and the stirring is carried out. After stirring for 20-30 minutes, sodium hydroxide solution is added to a pH value of 7, and the reaction is carried out for 20-25 hours to obtain a precursor;

[0014] Step B3: The precursor, modifier, benzoin dimethyl ether and DMF are mixed evenly, reacted for 2-3 hours at a speed of 150-200r / min, a temperature of 40-50°C and 365nm ultraviolet light irradiation, and then added to a muffle furnace, and calcined for 1.5-2 hours at a temperature of 800-900°C and an argon atmosphere to obtain a pretreated filler. The pretreated filler, polyvinyl pyrrolidone and deionized water are mixed evenly, stirred at a speed of 120-150r / min and a temperature of 20-25°C, and ethylenediamine is added to a pH value of 9.5-10, glucose is added, stirred for 10-15min, a silver nitrate solution is added, the temperature is raised to 60-65°C, and stirring is continued for 40-50min to obtain a conductive filler.

[0015] Furthermore, the amount ratio of cellulose, sodium hydroxide, anhydrous ethanol and chloroacetic acid described in step B1 is 5g:6g:150mL:6g, the molar ratio of carboxyl group, 2-aminoimidazole and dicyclohexylcarbodiimide on carboxymethyl cellulose is 1:1:1.2, the amount ratio of functionalized cellulose and thioglycolic acid is 1g:1mL, and the amount of p-toluenesulfonic acid is 1% by mass of thioglycolic acid.

[0016] Furthermore, the dosage ratio of tetramethylammonium hydroxide, methanol, vinyltrimethoxysilane and deionized water in step B2 is 135mmol:30mL:25mmol:1.5mL, and the dosage ratio of functionalized cellulose, 2-methylimidazole, deionized water and copper nitrate trihydrate is 1g:50mmol:80mmol:500mL.

[0017] Furthermore, the molar ratio of the thiol group on the precursor and the double bond on the modifier described in step B3 is 1:1, the amount of benzoin is 2‰ of the mass of the modifier, the amount ratio of the pretreated filler, polyvinyl pyrrolidone, deionized water, glucose and silver nitrate solution is 5g:2g:50mL:5g:10mL, and the silver nitrate solution is a mixture of silver nitrate, disodium ethylenediaminetetraacetic acid and deionized water in a ratio of 1mmol:1mmol:4mL.

[0018] Beneficial effects of the present invention: A conductive coating slurry for a dry electrode battery prepared by the present invention comprises the following raw materials: Li4Ti5O 12 , conductive filler and adhesive, the adhesive is reacted with thiophene-3-boric acid and p-bromobenzoic acid, so that the boronic acid group on the thiophene-3-boric acid reacts with the bromine atom site on the p-bromobenzoic acid to obtain intermediate 1, the intermediate 1 is reacted with acryl alcohol, so that the carboxyl group on the intermediate 1 is esterified with the acryl alcohol to obtain a modified monomer, hexafluoroisopropanol and acrylic acid are reacted, so that the hydroxyl group on the hexafluoroisopropanol is esterified with the carboxyl group on the acrylic acid to obtain a functional monomer, EVA, the functional monomer, the modified monomer and diisopropylbenzene peroxide are melt-extruded, and the functional monomer and the modified monomer are grafted with the EVA main chain under the action of diisopropylbenzene peroxide to obtain the adhesive.

[0019] The conductive filler takes cellulose as a raw material, is first treated with sodium hydroxide, and then reacted with chloroacetic acid, so that the sodium alcohol group reacts with the chlorine atom site on the chloroacetic acid to obtain carboxymethyl cellulose, the carboxymethyl cellulose is reacted with 2-aminoimidazole, so that the carboxyl group on the carboxymethyl cellulose and the amino group on the 2-aminoimidazole undergo dehydration reaction to obtain functionalized cellulose, the functionalized cellulose is reacted with thioglycolic acid, so that the remaining hydroxyl group on the functionalized cellulose and the carboxyl group on the thioglycolic acid are esterified to obtain modified cellulose, vinyltrimethoxysilane is hydrolyzed and condensed to form a cage-type silsesquioxane structure to obtain a modifier, the functionalized cellulose, 2-methylimidazole and copper nitrate trihydrate are reacted to form a cellulose composite copper organic framework to obtain a precursor, the precursor and the modifier are reacted under ultraviolet light irradiation conditions to graft the thiol group on the precursor with the double bond on the modifier, and then calcined in an argon atmosphere to obtain a pretreated filler, and finally treated with a silver nitrate solution to embed metallic silver in the pores on the surface of the pretreated filler to obtain a conductive filler.

[0020] The modified monomer and functional monomer contain thiophene structure, which makes the binder have a certain conductive effect. At the same time, the conjugated monomer contains fluorocarbon structure, which can improve the anti-corrosion effect of the binder. Compared with the traditional binder PVDF, it has a lower melting point and is more suitable for dry electrode hot pressing process. The conductive filler has a large number of through holes inside the organic framework of cellulose and copper. The through holes provide channels from the electrolyte to the electrode surface, which promotes charge transfer. The interconnected network reduces the contact resistance and improves the overall conductivity. The surface metallic silver further improves the conductivity. The silicon support structure inside ensures the structural integrity of the conductive filler during use. DETAILED DESCRIPTION

[0021] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] Example 1

[0023] A method for preparing a conductive coating slurry for a dry electrode battery comprises the following steps:

[0024] Step A1: Thiophene-3-boric acid, p-bromobenzoic acid, sodium methoxide and toluene are mixed evenly, and reacted at a speed of 150 r / min and a temperature of 65° C. for 2 h to obtain intermediate 1; intermediate 1, allyl alcohol, p-toluenesulfonic acid and toluene are mixed evenly, and reacted at a speed of 60 r / min and a temperature of 110° C. for 7 h to obtain a modified monomer;

[0025] Step A2: Hexafluoroisopropanol, acrylic acid, p-toluenesulfonic acid and toluene are uniformly mixed, and reacted at a speed of 60 r / min and a temperature of 110° C. for 5 hours to obtain a functional monomer, and EVA, functional monomer, modified monomer and dicumyl peroxide are added to a twin-screw extruder, and extruded and cooled under the conditions that the temperatures of zones 1 to 6 are 150° C., 155° C., 160° C., 170° C., 170° C., 170° C. and 170° C. to obtain a binder;

[0026] Step A3: Weigh the following raw materials by weight: 80 parts Li4Ti5O 12 , 10 parts of conductive filler and 10 parts of binder, mix the raw materials evenly to prepare a conductive coating slurry.

[0027] The molar ratio of thiophene-3-boric acid and p-bromobenzoic acid in step A1 is 1:1, the amount of sodium methoxide is 2% of the total mass of thiophene-2-boric acid and p-bromobenzoic acid, the molar ratio of intermediate 1 and allyl alcohol is 1:1, and the amount of p-toluenesulfonic acid is 1% of the total mass of intermediate 1 and acrylic acid.

[0028] The molar ratio of hexafluoroisopropanol and acrylic acid described in step A2 is 1:1, the amount of p-toluenesulfonic acid is 1.5% of the total mass of hexafluoroisopropanol and acrylic acid, the mass ratio of EVA, functional monomer, modified monomer and diisopropylbenzene peroxide is 100:15:8:2, and the model of EVA is VA55.

[0029] The conductive filler is prepared by the following steps:

[0030] Step B1: cellulose, sodium hydroxide and anhydrous ethanol are mixed evenly, reacted at a speed of 120 r / min and a temperature of 25°C for 1 hour, chloroacetic acid is added, the temperature is raised to 75°C, and the reaction is carried out for 2 hours to obtain carboxymethyl cellulose, carboxymethyl cellulose, 2-aminoimidazole, dicyclohexylcarbodiimide and DMF are mixed, and the reaction is carried out at a speed of 200 r / min and a temperature of 40°C for 4 hours to obtain functionalized cellulose, and functionalized cellulose, thioglycolic acid, sodium p-toluenesulfonate and toluene are mixed evenly, and the reaction is carried out at a speed of 60 r / min and a temperature of 110°C for 6 hours to obtain modified cellulose;

[0031] Step B2: Tetramethylammonium hydroxide and methanol are mixed evenly, nitrogen is introduced for protection, vinyltrimethoxysilane and deionized water are added under the conditions of a rotation speed of 150 r / min and a temperature of 20°C, and the reaction is carried out for 20 hours, the temperature is raised to 60°C, the reaction is carried out for 45 hours, and the pH value is adjusted to neutral to obtain a modifier, functionalized cellulose, 2-methylimidazole and deionized water are mixed evenly, copper nitrate trihydrate is added under the conditions of a rotation speed of 200 r / min and a temperature of 25°C, and the mixture is stirred for 20 minutes, and then sodium hydroxide solution is added to a pH value of 7, and the reaction is carried out for 20 hours to obtain a precursor;

[0032] Step B3: The precursor, modifier, benzoin dimethyl ether and DMF are mixed evenly, reacted for 2 hours at a speed of 150 r / min, a temperature of 40°C and 365nm ultraviolet light irradiation, and then added into a muffle furnace, and calcined for 1.5 hours at a temperature of 800°C and an argon atmosphere to obtain a pretreated filler. The pretreated filler, polyvinyl pyrrolidone and deionized water are mixed evenly, stirred at a speed of 120 r / min and a temperature of 20°C, and ethylenediamine is added to a pH value of 9.5, glucose is added, stirred for 10 minutes, silver nitrate solution is added, the temperature is raised to 60°C, and stirring is continued for 40 minutes to obtain a conductive filler.

[0033] The amount ratio of cellulose, sodium hydroxide, anhydrous ethanol and chloroacetic acid described in step B1 is 5g:6g:150mL:6g, the molar ratio of carboxyl group, 2-aminoimidazole and dicyclohexylcarbodiimide on carboxymethyl cellulose is 1:1:1.2, the amount ratio of functionalized cellulose and thioglycolic acid is 1g:1mL, and the amount of p-toluenesulfonic acid is 1% by mass of thioglycolic acid.

[0034] The amount ratio of tetramethylammonium hydroxide, methanol, vinyltrimethoxysilane and deionized water in step B2 is 135mmol:30mL:25mmol:1.5mL, and the amount ratio of functionalized cellulose, 2-methylimidazole, deionized water and copper nitrate trihydrate is 1g:50mmol:80mmol:500mL.

[0035] The molar ratio of the thiol group on the precursor and the double bond on the modifier described in step B3 is 1:1, the amount of benzoin is 2‰ of the mass of the modifier, the amount ratio of the pretreated filler, polyvinyl pyrrolidone, deionized water, glucose and silver nitrate solution is 5g:2g:50mL:5g:10mL, and the silver nitrate solution is mixed with silver nitrate, disodium ethylenediaminetetraacetic acid and deionized water in a ratio of 1mmol:1mmol:4mL.

[0036] Example 2

[0037] A method for preparing a conductive coating slurry for a dry electrode battery comprises the following steps:

[0038] Step A1: Thiophene-3-boric acid, p-bromobenzoic acid, sodium methoxide and toluene are mixed uniformly, and reacted at a speed of 200 r / min and a temperature of 65° C. for 2 h to obtain intermediate 1; intermediate 1, allyl alcohol, p-toluenesulfonic acid and toluene are mixed uniformly, and reacted at a speed of 80 r / min and a temperature of 115° C. for 8 h to obtain a modified monomer;

[0039] Step A2: Hexafluoroisopropanol, acrylic acid, p-toluenesulfonic acid and toluene are uniformly mixed, and reacted for 6 hours at a speed of 60 r / min and a temperature of 115° C. to obtain a functional monomer, and EVA, functional monomer, modified monomer and dicumyl peroxide are added into a twin-screw extruder, and extruded and cooled at temperatures of 150° C., 155° C., 160° C., 170° C., 170° C., 170° C. and 170° C. in zones 1 to 6 to obtain a binder;

[0040] Step A3: Weigh the following raw materials by weight: 90 parts of Li4Ti5O 12 , 13 parts of conductive filler and 13 parts of binder, mix the raw materials evenly to prepare a conductive coating slurry.

[0041] The molar ratio of thiophene-3-boric acid and p-bromobenzoic acid in step A1 is 1:1, the amount of sodium methoxide is 2% of the total mass of thiophene-2-boric acid and p-bromobenzoic acid, the molar ratio of intermediate 1 and allyl alcohol is 1:1, and the amount of p-toluenesulfonic acid is 1% of the total mass of intermediate 1 and acrylic acid.

[0042] The molar ratio of hexafluoroisopropanol and acrylic acid described in step A2 is 1:1, the amount of p-toluenesulfonic acid is 1.5% of the total mass of hexafluoroisopropanol and acrylic acid, the mass ratio of EVA, functional monomer, modified monomer and dicumyl peroxide is 100:15:8:3.5, and the model of EVA is VA55.

[0043] The conductive filler is prepared by the following steps:

[0044] Step B1: cellulose, sodium hydroxide and anhydrous ethanol are mixed evenly, reacted at a speed of 120 r / min and a temperature of 30°C for 1 hour, chloroacetic acid is added, the temperature is raised to 80°C, and the reaction is carried out for 2 hours to obtain carboxymethyl cellulose, carboxymethyl cellulose, 2-aminoimidazole, dicyclohexylcarbodiimide and DMF are mixed, and the reaction is carried out at a speed of 200 r / min and a temperature of 45°C for 5 hours to obtain functionalized cellulose, and functionalized cellulose, thioglycolic acid, sodium p-toluenesulfonate and toluene are mixed evenly, and the reaction is carried out at a speed of 60 r / min and a temperature of 115°C for 7 hours to obtain modified cellulose;

[0045] Step B2: Tetramethylammonium hydroxide and methanol are mixed evenly, nitrogen is introduced for protection, vinyltrimethoxysilane and deionized water are added under stirring at a speed of 150 r / min and a temperature of 25°C, and the reaction is carried out for 20 hours, the temperature is raised to 65°C, the reaction is carried out for 50 hours, and the pH value is adjusted to neutral to obtain a modifier, functionalized cellulose, 2-methylimidazole and deionized water are mixed evenly, copper nitrate trihydrate is added under stirring at a speed of 200 r / min and a temperature of 28°C, and after stirring for 25 minutes, sodium hydroxide solution is added to a pH value of 7, and the reaction is carried out for 25 hours to obtain a precursor;

[0046] Step B3: The precursor, modifier, benzoin dimethyl ether and DMF are mixed evenly, reacted for 2.5 hours at a speed of 150 r / min, a temperature of 45°C and 365nm ultraviolet light irradiation, and then added to a muffle furnace and calcined for 2 hours at a temperature of 850°C in an argon atmosphere to obtain a pretreated filler. The pretreated filler, polyvinyl pyrrolidone and deionized water are mixed evenly, stirred at a speed of 120 r / min and a temperature of 20°C, and ethylenediamine is added to a pH value of 10, glucose is added, stirred for 15 minutes, a silver nitrate solution is added, the temperature is raised to 60°C, and stirring is continued for 45 minutes to obtain a conductive filler.

[0047] The amount ratio of cellulose, sodium hydroxide, anhydrous ethanol and chloroacetic acid described in step B1 is 5g:6g:150mL:6g, the molar ratio of carboxyl group, 2-aminoimidazole and dicyclohexylcarbodiimide on carboxymethyl cellulose is 1:1:1.2, the amount ratio of functionalized cellulose and thioglycolic acid is 1g:1mL, and the amount of p-toluenesulfonic acid is 1% by mass of thioglycolic acid.

[0048] The amount ratio of tetramethylammonium hydroxide, methanol, vinyltrimethoxysilane and deionized water in step B2 is 135mmol:30mL:25mmol:1.5mL, and the amount ratio of functionalized cellulose, 2-methylimidazole, deionized water and copper nitrate trihydrate is 1g:50mmol:80mmol:500mL.

[0049] The molar ratio of the thiol group on the precursor and the double bond on the modifier described in step B3 is 1:1, the amount of benzoin is 2‰ of the mass of the modifier, the amount ratio of the pretreated filler, polyvinyl pyrrolidone, deionized water, glucose and silver nitrate solution is 5g:2g:50mL:5g:10mL, and the silver nitrate solution is mixed with silver nitrate, disodium ethylenediaminetetraacetic acid and deionized water in a ratio of 1mmol:1mmol:4mL.

[0050] Example 3

[0051] A method for preparing a conductive coating slurry for a dry electrode battery comprises the following steps:

[0052] Step A1: Thiophene-3-boric acid, p-bromobenzoic acid, sodium methoxide and toluene are mixed evenly, and reacted at a speed of 200 r / min and a temperature of 70° C. for 3 h to obtain intermediate 1; intermediate 1, allyl alcohol, p-toluenesulfonic acid and toluene are mixed evenly, and reacted at a speed of 80 r / min and a temperature of 120° C. for 8 h to obtain a modified monomer;

[0053] Step A2: Hexafluoroisopropanol, acrylic acid, p-toluenesulfonic acid and toluene are uniformly mixed, and reacted at a speed of 80 r / min and a temperature of 120° C. for 6 hours to obtain a functional monomer, and EVA, functional monomer, modified monomer and dicumyl peroxide are added into a twin-screw extruder, and extruded and cooled under the conditions that the temperatures of zones 1 to 6 are 150° C., 155° C., 160° C., 170° C., 170° C., 170° C. and 170° C. to obtain a binder;

[0054] Step A3: Weigh the following raw materials by weight: 100 parts Li4Ti5O 12 , 15 parts of conductive filler and 15 parts of binder, mix the raw materials evenly to prepare a conductive coating slurry.

[0055] The molar ratio of thiophene-3-boric acid and p-bromobenzoic acid in step A1 is 1:1, the amount of sodium methoxide is 2% of the total mass of thiophene-2-boric acid and p-bromobenzoic acid, the molar ratio of intermediate 1 and allyl alcohol is 1:1, and the amount of p-toluenesulfonic acid is 1% of the total mass of intermediate 1 and acrylic acid.

[0056] The molar ratio of hexafluoroisopropanol and acrylic acid described in step A2 is 1:1, the amount of p-toluenesulfonic acid is 1.5% of the total mass of hexafluoroisopropanol and acrylic acid, the mass ratio of EVA, functional monomer, modified monomer and dicumyl peroxide is 100:15:8:5, and the model of EVA is VA55.

[0057] The conductive filler is prepared by the following steps:

[0058] Step B1: cellulose, sodium hydroxide and anhydrous ethanol are mixed evenly, reacted at a speed of 150 r / min and a temperature of 30°C for 1.5 hours, chloroacetic acid is added, the temperature is raised to 80°C, and the reaction is carried out for 3 hours to obtain carboxymethyl cellulose, carboxymethyl cellulose, 2-aminoimidazole, dicyclohexylcarbodiimide and DMF are mixed, and the reaction is carried out at a speed of 300 r / min and a temperature of 50°C for 6 hours to obtain functionalized cellulose, and functionalized cellulose, thioglycolic acid, sodium p-toluenesulfonate and toluene are mixed evenly, and the reaction is carried out at a speed of 80 r / min and a temperature of 120°C for 8 hours to obtain modified cellulose;

[0059] Step B2: Tetramethylammonium hydroxide and methanol are mixed evenly, nitrogen is introduced for protection, vinyltrimethoxysilane and deionized water are added under the conditions of a rotation speed of 200 r / min and a temperature of 25°C, and the reaction is carried out for 25 hours, the temperature is raised to 70°C, the reaction is carried out for 50 hours, and the pH value is adjusted to neutral to obtain a modifier, and functionalized cellulose, 2-methylimidazole and deionized water are mixed evenly, copper nitrate trihydrate is added under the conditions of a rotation speed of 300 r / min and a temperature of 30°C, and the stirring is carried out for 30 minutes, and sodium hydroxide solution is added to a pH value of 7, and the reaction is carried out for 25 hours to obtain a precursor;

[0060] Step B3: The precursor, modifier, benzoin dimethyl ether and DMF are mixed evenly, reacted for 3 hours at a speed of 200 r / min, a temperature of 50°C and 365nm ultraviolet light irradiation, and then added into a muffle furnace, and calcined for 2 hours at a temperature of 900°C and an argon atmosphere to obtain a pretreated filler. The pretreated filler, polyvinyl pyrrolidone and deionized water are mixed evenly, stirred at a speed of 150 r / min and a temperature of 25°C, and ethylenediamine is added to a pH value of 10, glucose is added, stirred for 15 minutes, silver nitrate solution is added, the temperature is raised to 65°C, and stirring is continued for 50 minutes to obtain a conductive filler.

[0061] The amount ratio of cellulose, sodium hydroxide, anhydrous ethanol and chloroacetic acid described in step B1 is 5g:6g:150mL:6g, the molar ratio of carboxyl group, 2-aminoimidazole and dicyclohexylcarbodiimide on carboxymethyl cellulose is 1:1:1.2, the amount ratio of functionalized cellulose and thioglycolic acid is 1g:1mL, and the amount of p-toluenesulfonic acid is 1% by mass of thioglycolic acid.

[0062] The amount ratio of tetramethylammonium hydroxide, methanol, vinyltrimethoxysilane and deionized water in step B2 is 135mmol:30mL:25mmol:1.5mL, and the amount ratio of functionalized cellulose, 2-methylimidazole, deionized water and copper nitrate trihydrate is 1g:50mmol:80mmol:500mL.

[0063] The molar ratio of the thiol group on the precursor and the double bond on the modifier described in step B3 is 1:1, the amount of benzoin is 2‰ of the mass of the modifier, the amount ratio of the pretreated filler, polyvinyl pyrrolidone, deionized water, glucose and silver nitrate solution is 5g:2g:50mL:5g:10mL, and the silver nitrate solution is mixed with silver nitrate, disodium ethylenediaminetetraacetic acid and deionized water in a ratio of 1mmol:1mmol:4mL.

[0064] Comparative Example 1

[0065] Compared with Example 1, no modified monomer was added in this comparative example, and the remaining steps were the same.

[0066] Comparative Example 2

[0067] Compared with Example 1, no functional monomer was added in this comparative example, and the remaining steps were the same.

[0068] Comparative Example 3

[0069] Compared with Example 1, no functionalized cellulose was added in this comparative example, and the remaining steps were the same.

[0070] Comparative Example 4

[0071] Compared with Example 1, this comparative example uses pretreated filler instead of conductive filler, and the other steps are the same.

[0072] The conductive coating slurry prepared in Examples 1-3 and Comparative Examples 1-4 was sprayed on aluminum foil, hot pressed and cut into pieces with a diameter of 13 mm. Celgard 2500 diaphragm, gasket, and shrapnel were used. The battery shell was a complete set of CR2032 button battery materials, and the electrolyte was LiPF6 (ethylene carbonate, dimethyl carbonate, and diethyl carbonate in a volume ratio of 1:1:1) to make battery samples.

[0073] Under the conditions of voltage of 1.5V and constant current of 0.2C, after charging and discharging 6 times, discharge to 0.01V with a constant current of 0.5C, and then charge to 1.5V with a constant current of 0.5C. This discharge and recharge is counted as one cycle, until the cycle is 500 times, 800 times, and 1000 times. Calculate the battery capacity retention rate. The results are shown in the following table.

[0074] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 500 times 90.22 90.35 90.43 90.13 90.07 76.23 88.45 800 times 89.37 89.54 89.36 89.22 89.14 71.59 85.21 1000 times 87.25 87.41 87.32 86.83 85.48 61.31 79.66

[0075] It can be seen from the above table that this application can improve the battery capacity retention rate and increase the battery life.

[0076] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a conductive coating slurry for a dry electrode battery, characterized in that: The specific steps include: Step A1: thiophene-3-boric acid, p-bromobenzoic acid, sodium methoxide and toluene are mixed and reacted to obtain an intermediate 1, and the intermediate 1, allyl alcohol, p-toluenesulfonic acid and toluene are mixed and reacted to obtain a modified monomer; Step A2: Hexafluoroisopropanol, acrylic acid, p-toluenesulfonic acid and toluene are mixed and reacted to obtain a functional monomer, and EVA, the functional monomer, the modified monomer and dicumyl peroxide are added into a twin-screw extruder, extruded and cooled to obtain a binder; Step A3: Weigh the following raw materials by weight: 80-100 parts of Li4Ti5O 12 , 10-15 parts of conductive filler and 10-15 parts of binder, mix the raw materials evenly to prepare a conductive coating slurry.

2. The method for preparing a conductive coating slurry for a dry electrode battery according to claim 1, characterized in that: The molar ratio of thiophene-3-boric acid to p-bromobenzoic acid in step A1 is 1:1, and the molar ratio of intermediate 1 to allyl alcohol is 1:

1.

3. The method for preparing a conductive coating slurry for a dry electrode battery according to claim 1, characterized in that: The molar ratio of hexafluoroisopropanol and acrylic acid in step A2 is 1:1, and the mass ratio of EVA, functional monomer, modified monomer and dicumyl peroxide is 100:15:8:2-5.

4. The method for preparing a conductive coating slurry for a dry electrode battery according to claim 1, characterized in that: The conductive filler is prepared by the following steps: Step B1: After cellulose, sodium hydroxide and anhydrous ethanol are mixed for reaction, chloroacetic acid is added, and the temperature is raised to react to obtain carboxymethyl cellulose; carboxymethyl cellulose, 2-aminoimidazole, dicyclohexylcarbodiimide and DMF are mixed for reaction to obtain functionalized cellulose; functionalized cellulose, thioglycolic acid, sodium p-toluenesulfonate and toluene are mixed for reaction to obtain modified cellulose; Step B2: Tetramethylammonium hydroxide and methanol are uniformly mixed, nitrogen is introduced for protection, vinyltrimethoxysilane and deionized water are added for reaction, and the pH value is adjusted to be neutral to obtain a modifier, functionalized cellulose, 2-methylimidazole and deionized water are mixed and stirred, copper nitrate trihydrate is added, and after stirring, sodium hydroxide solution is added to a pH value of 7 for reaction to obtain a precursor; Step B3: After the precursor, modifier, benzoin dimethyl ether and DMF are mixed and reacted, they are added into a muffle furnace and calcined to obtain a pretreated filler. The pretreated filler, polyvinyl pyrrolidone and deionized water are mixed and stirred, and ethylenediamine is added. Glucose is added and stirred. Silver nitrate solution is added. The temperature is raised and stirred to obtain a conductive filler.

5. The method for preparing a conductive coating slurry for a dry electrode battery according to claim 4, characterized in that: The amount ratio of cellulose, sodium hydroxide, anhydrous ethanol and chloroacetic acid described in step B1 is 5g:6g:150mL:6g, the molar ratio of carboxyl group, 2-aminoimidazole and dicyclohexylcarbodiimide on carboxymethyl cellulose is 1:1:1.2, and the amount ratio of functionalized cellulose and thioglycolic acid is 1g:1mL.

6. The method for preparing a conductive coating slurry for a dry electrode battery according to claim 4, characterized in that: The amount ratio of tetramethylammonium hydroxide, methanol, vinyltrimethoxysilane and deionized water in step B2 is 135mmol:30mL:25mmol:1.5mL, and the amount ratio of functionalized cellulose, 2-methylimidazole, deionized water and copper nitrate trihydrate is 1g:50mmol:80mmol:500mL.

7. The method for preparing a conductive coating slurry for a dry electrode battery according to claim 4, characterized in that: The molar ratio of the thiol group on the precursor and the double bond on the modifier described in step B3 is 1:1, the amount ratio of the pretreated filler, polyvinyl pyrrolidone, deionized water, glucose and silver nitrate solution is 5g:2g:50mL:5g:10mL, and the silver nitrate solution is a mixture of silver nitrate, disodium ethylenediaminetetraacetic acid and deionized water in a ratio of 1mmol:1mmol:4mL.

8. Use of the conductive coating slurry according to any one of claims 1 to 7 in a dry electrode battery.

Citation Information

Patent Citations

  • In-situ synthesis preparation method and application of cellulose / metal organic framework compound

    CN106995531A

  • Polymer micro-nano binder as well as preparation and application thereof

    CN115785849A

  • Dry-method electrode plate, preparation method thereof and battery containing dry-method electrode plate

    CN115911260A

  • High-impact conductive polyamide composite material and preparation method thereof

    CN118546523A

  • Conductive slurry for photovoltaic cell and preparation method thereof

    CN118571526A